Treatment of canine nasopharyngeal stenosis using balloon‐expandable metallic stents: long‐term follow‐up of four cases. (24th December 2015) - Bird, L.; Nelissen, P.; White, R. A. S.; Tappin, S. W.
Abstract : Four dogs were diagnosed with nasopharyngeal stenosis usinge ndoscopy and magnetic resonance imaging. Treatment using balloon‐expandable metallic stent, placed under fluoroscopic and endoscopic guidance, resulted in immediate resolution of clinical signs. All dogs were clinically normal 40 to 62 months following stent placement.